Performance of three transducer mounting methods in impedance-based structural health monitoring applications - da Silveira, Ricardo Zanni Mendes [UNESP]; Campeiro, Leandro Melo [UNESP]; Baptista, Fabricio Guimarães [UNESP] (My University, 2017)
Piezoelectric transducers are widely used in many nondestructive methods for damage detection in structural health monitoring applications. Among the various methods for detecting damage, the electromechanical impedance technique is known for using thin and small piezoelectric ceramics operating simultaneously as actuators and sensors. The basic method of installing these piezoelectric ceramics in the host structure is using a high-stiffness adhesive such as epoxy or cyanoacrylate glue. However, some studies have proposed alternative methods of transducer mounting, therein aiming to reuse the transducer or allowing for the monitoring of structures under adverse conditions under which the direct installation of the sensor would not be possible. Thus, the objective of this study is to analyze and compare the performance of three main mounting methods for metal structures for applications based on the electromechanical impedance technique: magnetic mounting, metal-wire-based mounting, and conventional mounting using adhesives. Tests were conducted on aluminum beams, and the performances of the three transducer mounting methods were compared using basic damage indices and the pencil-lead-break test. The experimental results indicate that the mounting method has a significant effect on the frequency response and sensitivity for damage detection.
Keywords: damage; electromechanical impedance; mounting; piezoelectric transducer; structural health monitoring